Emerging Trends in Pakistan’s Economy: Implications of Pakistan-China Relations - Naseeb, Zoonia; Khalid, Iram (Annals of Human and Social Sciences, 2022)
The objective of the study is to explore new avenues in their relationship that have all the glory in the past, all the cooperation in the present and all the development and achievements in the coming future. Pakistan is exploring new trends in its economy where China, its long-standing partner, is providing the evident support for Pakistan to achieve its goals. Pakistan and China have developed their long-standing diplomatic relations in tough years of superpowers rivalry in the cold war period, and now are on the highest level with successive achievements in various fields and understanding the importance of their geostrategic location for economic activities. The bilateral relations of both states has multidimensional cooperation, covering all the fields economic, and social, cultural and people to people contact. The methodology is descriptive. The implication of economic plans will make Pakistan a competitive participant in the region and open a new phase for regional development.